How to Reduce Mental Health Burden in Health Care Workers During COVID-19?–A Scoping Review of Guideline Recommendations - Halms, Theresa; Strasser, Martina; Kunz, Miriam; Hasan, Alkomiet (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic has posed an unprecedented demand and a huge burden for healthcare workers (HCWs) worldwide, with alarming reports of heightened mental health problems. To counteract these mental health challenges, guidelines and recommendations for the support of HCWs during the COVID-19 pandemic have been published. With this scoping review and guideline evaluation, we aim to provide a critical overview of these guidelines and recommendations and to guide policy makers in establishing respective surveillance and care programs. In summary, 41 articles were included in this review which were published between April 2020 and May 2021. Across all articles, the guidelines and recommendations could be clustered into 4 main categories: “Social/structural support”, “Work environment”, “Communication/Information”, “Mental health support”. Although there was substantial agreement across articles about the recommendations given, empirical evidence on the effectiveness of these recommendations is still lacking. Moreover, most recommendations were developed without involving different members of the target group (HCWs) or other involved stakeholders. Strategies to detect potential barriers and to implement these guidelines in clinical practice are lacking.